Motivasi Kerja, Disiplin Kerja, dan Komitmen Organisasional terhadap Kinerja Pegawai pada Organisasi Sektor Publik - Sri Wahyu Utama; Sjarief Hidajat (Journal of Management and Bussines (JOMB), 2022)
This study aims to determine and prove the influence of work motivation, work discipline, and organizational commitment on employee performance in public sector organizations (studies at the Mojokerto Regency Library and Archives Service). This research was conducted using a quantitative method through a questionnaire with four variables, namely work motivation (X1), work discipline (X2), organizational commitment (X3) and employee performance variables (Y). The analysis technique that will be used in this study uses Multiple Linear Regression Analysis, Coefficient of Determination (R2), F test, and T test. The results of the study show that the results of multiple linear regression analysis yield the equation Y = 0.846 + 0.603X1 + 0.354X2 + 0.108 X3 + e. Then based on this analysis the value of R square (R2) is 0.814 or 81.4%. The R2 value states that motivation (X1), work discipline (X2), and organizational commitment (X3) contribute 81.4% to employee performance (Y). Meanwhile, the remaining 18.6% is influenced by other variables not examined in the course of this study. In conclusion, the simultaneous effect of work motivation, work discipline, and organizational commitment on employee performance. Keywords: Work Discipline, Performance, Organizational Commitment, Work Motivation